Analisis Tingkat Kepatuhan TPS Limbah B3 IPLT Keputih Surabaya Berdasarkan PERMENLHK No 6 Tahun 2021 - Nadia Artanti, Putri; Agung Rachmanto, Tuhu (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The Keputih Surabaya Fecal Sludge Treatment Plant (IPLT) produces Hazardous and Toxic (B3) waste such as used lubricating oil, used rags, used batteries, and electronic waste with a total generation of 109,135 kg/year. This study analyses the compliance level of B3 waste temporary storage sites based on PERMENLHK No. 6 of 2021. The research method used descriptive analysis with an evaluation of 22 regulatory parameters. Results showed a compliance rate of 72% (16 out of 22 provisions met). Compliant aspects include building construction, packaging characteristics, and storage time. Deficiencies are found in B3 symbols and labels, emergency response facilities, drainage channels, and spill containment containers. Recommendations include the addition of B3 symbols and labels, provision of emergency response facilities (fire extinguisher, first aid kit, emergency shower), construction of drainage channels, and special containment containers for B3 waste spills.